The role of the volcano-tectonic structure on the seismic site response: An application in the northeastern sector of Mt. Etna volcano, Sicily, Italy - IMPOSA, Sebastiano (Contributions to Geophysics and Geodesy, 2021)
In this work, the author describes the results of a study aimed at verifying whether the technique of the spectral ratio (Nakamura, 1989) between horizontal and vertical components of an earthquake can also be applied to volcanic areas to estimate the site response. Five earthquakes have been considered to achieve this objective. These were recorded at the digital seismic station, equipped with a 3D seismometer, situated at Vena in the northeastern sector of Etna, in an area where the volcanic rocks have a modest thickness and lay on the quaternary clays and on flysch. The epicenters of the seismic events are located roughly along an arc of 130°, with vertices at the Vena seismic station. By considering the S radiation in the frequency domain, a preliminary deconvolution of the recorded seismic signal was performed. Then, the relationship H (f ) = (hu (f )2 + hv (f )2)1/2 was calculated, which represents the transfer function of the seismic signal through several surface layers, or rather the site amplification. In the first instance, and on the basis of the obtained results, by analyzing only the effects related to five seismic events opportunely distributed with respect to the central axis of the magma uprise, one must conclude that this response shows an appreciable anisotropy, probably determined by the complex volcano-tectonic structure of the area where the seismic station is located. Lastly, an analysis of the noise, to which the technique of the spectral ratio was applied, was performed in the frequency domain. Analogously to what was observed for the S waves, the amplification is markedly variable at the low frequencies and this, according to the author, is due to the temporal variation in the structure of the seismic signal.